Effect of dispersion of metallic tin and silicon carbide on the ionic conductivity of B2O3Li2OLiCl glasses - Parkash O.; Kumar D.; Gupta A. (My University, 2025)
B2O3Li2OLiCl glasses containing varying amounts of fine dispersion of silicon carbide and tin particulates have been prepared. Microstructural studies have been carried out using scanning electron microscope. Electrical conductivity measurements in the temperature range 300-575 K show that initially the conductivity increases with addition of dispersoid when the dispersed particles are uniformly distributed in the glassy matrix. Further addition of these in the glass leads to their agglomeration and the ionic conductivity decreases. This enhancement of ionic conductivity is similar to that of polycrystalline dispersed solid electrolytes. © 1987.